Gastronomical Practices and Sustainable Ecotourism Development: Insights from Two Eco-Destinations in Southwest Nigeria - Ndasule, Nora; OYELEKE, Olaide; Oladeji, Sunday (Journal of Science, Technology and Innovation Research, 2026)
Abstract This study presents findings from an assessment of management styles applied to gastronomical practices in selected ecotourism destinations in Lagos and Oyo States, Nigeria.he evaluation integrates structured questionnaires and stakeholder feedback to examine key managerial components such as decision-making regarding menu changes, staff involvement, training on local gastronomy, resource allocation, responsiveness to culinary trends, and communication effectiveness. A total of 10 key questionnaire items were rated by staff and management respondents across multiple ecotourism sites, capturing perspectives on how gastronomical activities are managed and improved. Data analysis techniques such as descriptive statistics and mean score interpretation was employed to evaluate the extent of agreement with each management indicator. Results indicate strong positive perceptions in areas such as innovation encouragement, resource allocation, and staff engagement, with an overall mean score of 3.93—suggesting supportive and participatory management styles. However, the findings also highlight areas needing enhancement, particularly flexibility in adapting menus and responsiveness to staff suggestions. The study provides actionable insights for refining gastronomical management practices within ecotourism, contributing to more sustainable and culturally enriching tourist experiences in developing regional destinations.